What Mission Statements Say: Signaling the Priority of Leadership Development - Brittany Devies; Kathy L. Guthrie (Journal of Higher Education Policy and Leadership Studies, 2022)
Higher education has made leadership development an evident priority. This study examines institutional mission statements from the Integrated Postsecondary Educational Data System (IPEDS), of which 842 statements include the words “leader(s)” and/or “leadership” with the aim to provide context about institutional commitment to leadership. This content analysis reveals how the concepts of leader and leadership are described, contextualized, operationalized, and how purpose is framed for institutions who include this language in their mission statements. With only 16% of all institutional mission statements including leadership terminology, the authors explore the implications of how the terminology presents itself within the data and what it means that a majority of institutional mission statements do not include leadership development as a priority. Analysis on the content of mission statements who included leader and leadership in their mission statements is explored. Finally, implications about contextualizing and operationalizing these findings are presented.